INFLUENCE OF THERMOPLASTIC PROCESSING PARAMETERS ON THEIR INTERNAL TEMPERATURE - Campos, F. A. R.; da Silva, L. R. R. (Revista de Engenharia Térmica, 2021)
With technological advances, polymers are increasingly used to manufacture various components that were previously exclusively manufactured with metals. One of the significant challenges in polymer processing is its relatively low thermal resistance, since relatively small temperature variations, especially when compared to metals and ceramics, lead to significant changes in material properties and in the final component geometry. This paper investigated how the internal temperature of polymers, subjected to an intermittent particulate jet deposition process in conjunction with a continuous flow of hot air, is affected by variation in surface roughness, polymer type, and air pressure. As the main result, low efficiency in heat transfer was caused by the combination of the convective nature of the heat exchange with the low thermal conductivity of the polymers. The variables with the most significant influence on the process were the intermittence and pressure of the particulate jet.